2019
DOI: 10.1183/16000617.0126-2018
|View full text |Cite
|
Sign up to set email alerts
|

The time-controlled adaptive ventilation protocol: mechanistic approach to reducing ventilator-induced lung injury

Abstract: Airway pressure release ventilation (APRV) is a ventilator mode that has previously been considered a rescue mode, but has gained acceptance as a primary mode of ventilation. In clinical series and experimental animal models of extrapulmonary acute respiratory distress syndrome (ARDS), the early application of APRV was able to prevent the development of ARDS. Recent experimental evidence has suggested mechanisms by which APRV, using the time-controlled adaptive ventilation (TCAV) protocol, may reduce lung inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 108 publications
(161 reference statements)
0
17
0
Order By: Relevance
“…Our TCAV method using the APRV mode has been discussed in detail elsewhere (Habashi, 2005;Jain et al, 2016;Nieman et al, 2018Nieman et al, , 2019Kollisch-Singule et al, 2019). Briefly, TCAV consists of an extended (4-5 s) open valve continuous positive airway pressure (CPAP) phase with a very short (≤0.5 s) release phase.…”
Section: The Tcav Methods To Open and Stabilize The Acutely Injured Lungmentioning
confidence: 99%
“…Our TCAV method using the APRV mode has been discussed in detail elsewhere (Habashi, 2005;Jain et al, 2016;Nieman et al, 2018Nieman et al, , 2019Kollisch-Singule et al, 2019). Briefly, TCAV consists of an extended (4-5 s) open valve continuous positive airway pressure (CPAP) phase with a very short (≤0.5 s) release phase.…”
Section: The Tcav Methods To Open and Stabilize The Acutely Injured Lungmentioning
confidence: 99%
“…“Trapping” of air based on a time is the key element of this ventilatory strategy and results in an auto-peep that stabilizes the lung by minimizing the alveolar size variation during expiration. Initial in vivo animal experiments showed that with a cutoff of 75%, most of the exhaled air was from the conducting airways with a minimal change in the alveolar size ( Nieman et al, 2018 ; Kollisch-Singule et al, 2019 ) thereby “splinting” the alveoli open. This air splint, in theory, minimizes atelectrauma and maximizes the maintenance of recruitment.…”
Section: The Airway Pressure Release Ventilation With Time-controlled...mentioning
confidence: 99%
“…Interestingly, in a porcine model of severe smoke inhalation injury, Batchinsky and colleagues found that APRV-treated animals developed ARDS faster than those treated with conventional volume-controlled ventilation [7]. Proponents argue that APRV improves alveolar recruitment and stability, improves ventilation-perfusion matching, increases mean airway pressure, minimizes peak and plateau pressures, preserves spontaneous breathing, and reduces sedation requirements [34][35][36]. Reduced sedation preserves airway reflexes and cough, and has the theoretical benefits in burn patients of reducing ventilator-associated pneumonia and increasing rehabilitation performance.…”
Section: Airway-pressure-release Ventilationmentioning
confidence: 99%